PENDAMPINGAN GURU PAUD DALAM PENGEMBANGAN INOVASI KURIKULUM BERBASIS PEMBELAJARAN BERDIFERENSIASI UNTUK MEWUJUDKAN LAYANAN INKLUSIF DI PAUD - Elina Intan Apriliani; Muhammad Fathurrahman; Annafi’ Nurul ‘Ilmi Azizah (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to strengthen the capacity of early childhood education (ECE) teachers in developing curriculum innovation through the implementation of differentiated learning to support inclusive practices in PAUD (Indonesian early childhood education institutions). The program was implemented through three main stages: needs assessment, capacity-building workshops, and classroom mentoring. A participatory approach was applied to ensure active involvement of teachers throughout the process. Findings show that teachers initially had limited understanding of differentiated learning and tended to apply uniform activities for all children. After participating in workshops and coaching clinics, teachers demonstrated significant improvement in designing lesson plans that incorporated variations in content, process, and product based on children’s readiness, interests, and learning profiles. Classroom mentoring revealed increased teacher confidence in managing differentiated activities and facilitating more inclusive interactions. Teachers also showed better skills in conducting diagnostic assessments and using the results to plan subsequent learning activities. Overall, the program effectively enhanced teachers’ pedagogical competence, improved classroom practices, and fostered a more inclusive and responsive learning environment in PAUD settings. These outcomes indicate that continuous mentoring and collaborative professional development are essential for supporting the successful implementation of differentiated learning within the framework of the Merdeka Curriculum.